Human Rights and Transnational Distributive Justice - Martin, J. Paul (2009)
This paper addresses transnational distributive justice in relation to human rights and state obligations regarding the distribution of wealth. International cooperation and the elimination of poverty are aspects developed throughout the article with the aim of answering the question as to what are the obligations of States to each other. In this sense, the author analyzes whether we are faced with an established obligation with respect to other States or whether we are on a minimum floor that can be satisfied with the attention or coverage of basic needs. Thus, the author reflects on the role of international organizations and their practices in matters of transnational distributive justice, analyzing, for example, the actions of the UN, the World Bank and the World Trade Organization.